A Literature Review on the influence of online services adoption in enhancing the experience of modern banking - Sharma, Anupam (International Journal of Psychosocial Rehabilitation, 2020)
-Online channel of banking has brought a drastic change in the field of modern banking. It is the outcome of latest technological advancements which is strongly creating an impact in the lives of people. This concept has made a phenomenal transformation in the pattern of delivery of banking services to the customers. This paper is presenting a review analysis to some of the eminent researches conducted earlier with the purpose of measuring the impact of adoption of online system of banking on the behavioural patterns of the users. This analysis also explains about the possible impact of the online channel of service distribution on the overall growth and development of modern banking.